Facts about Wildlife Diseases: Rabbit Hemorrhagic Disease Virus Serotype 2 (RHDV2) - Catherine E. Dixon; Juan M. Campos Krauer (EDIS)
This publication provides information on rabbit hemorrhagic disease virus serotype 2 (RHDV2) and discusses infection, clinical signs, treatment, prevention, and reporting. Written by Catherine E. Dixon and Juan M. Campos Krauer, and published by the UF College of Veterinary Medicine, April 2022.